(SJ FUFYPA VXJP SURV[RNLMJ FMSALEFYVJ XRORV D (B/ (SSRLRXJXA(B, (SSURBNJOAXA MAL RUDAP]VJ XJV SURV[RNLMJV FMSALEFYVJVs - (SMryuxj Fygacc(Sfnlgas ((SXys}kjx}(B,s, 2002)
(SSURV[RNLMJ MAL SU]XRV[RNLMJ FMSALEFYVJ KFOAXA ZLNRVRZLAV XJV SALEFLAV URNRV(B, (SAPASAUAVXAVFLV MAL FMSALEFYVJ FMSALEFYXLM]Ps
(SSURV[RNLMJ MAL SU]XRV[RNLMJ FMSALEFYVJ KFOAXA ZLNRVRZLAV XJV SALEFLAV URNRV(B, (SAPASAUAVXAVFLV MAL FMSALEFYVJ FMSALEFYXLM]Ps